The dilemma of Work-Integrated Learning (WIL) in South African higher education - the case of Town and Regional Planning at the University of Johannesburg - Lewis, Martin; Holtzhausen, Natasja; Taylor, Susanne (Department of Urban and Regional Planning, University of the Free State, 2010)
English: The South African Higher Education Qualifications Framework (HEQF) gazetted in 2007 sets a revised qualifications framework that necessitates the re-evaluation and redesign of programmes to align with the new framework. For the first time the HEQF introduced the term 'Work-Integrated Learning' (WIL) into a Department of Education document with possible legal consequences for institutions of higher education, as the framework document provides that higher education institutions offering qualifications with a WIL component must place the students. This has led to a dilemma as placements are not always readily available. In addition, there is 'pressure' within institutions and from certain faculty members to eliminate the WIL component from curricula. This article aims to answer the following questions: - Is it worth retaining WIL in the Town and Regional Planning academic programme? - If it is found that WIL should remain part of the qualification, when should the students engage with this component? - If it is found that WIL should remain part of the qualification, for how long should this component be offered? This article presents the findings of the qualitative study aimed at finding a solution to the dilemma relating to WIL, with students from industry being surveyed for their input. It, therefore, forms part of what is an ongoing dialogue concerning all aspects relating to appropriate education.

Afrikaans: Die Suid-Afrikaanse Hoër Onderwys Kwalifikasie Raamwerk (Higher Education Qualifications Framework - HEQF), soos in 2007 gepubliseer, stel 'n gewysigde kwalifikasieraamwerk daar wat die herevalueering en herontwerp van programme vereis om binne die nuwe raamwerk in te pas. Vir die eerste keer gebruik die HEQF die term 'Work-Integrated Learning' (WIL) in n dokument van die Departement van Onderwys, met moontlike regsimplikasies vir hoër onderwys, aangesien die raamwerk dokument voorsiening maak dat Hoëronderwysinstellings wat kwalifikasies aanbied met 'n Werksgeïntegreerde Leerkomponent studente moet plaas. Dit het gelei tot 'n dilemma aangesien plasingsmoontlikhede nie altyd geredelik beskikbaar is nie. Daar word druk binne instansies en deur sekere fakulteitslede uitgeoefen om die WIL-module uit die kurrikulum te verwyder. Die artikel het ten doel om die volgende vrae te beantwoord: - Is dit die moeite werd om WIL in die Stad en Streekbeplanning akademiese program te behou? - Indien die bevinding is dat WIL as deel van die kwalifikasie moet bly, wanneer behoort studente die komponent te neem? - Indien dit bevind word dat WIL deel van die kwalifikasie moet bly, hoe lank moet die komponent wees? Hierdie artikel gee die bevindinge weer van 'n kwalitatiewe studie wat daarop gerig is om 'n oplossing te vind vir die dilemma met betreking tot 'WIL'. In die studie is studente en bedryfsvennote vir hulle insette genader. Die studie vorm dus deel van 'n voortgesette dialoog oor al die aspekte van toepaslike onderwys.

SeSotho: Lekgotla la dikolo tsa dithuto tse dikgolo mo Afrika Borwa le le neng le kopane ka 2007 le tlhomile melawana e e tlhokwang go lebelelwa le go ntšhwafadiwa gape go ya ka melawana e mešwa e e tlhomilweng. Lekgotla le, le ne la tsisa la ntlha mo Lefapheng la Thuto, lenaane le le kopantseng go ikatisetsa go dira le go ithuta ka nako e le nngwe. Lenaane le, le na le ditlamorago tsa semolao go dikolo tsa dithuto tse dikgolo tse di sa le diriseng ka tshwanelo. Bao ba le dirisang, ba tshwanetse ke go bona fa baithuti ba bona diphatla tiro tsa go ka ikatisetsa tiro ba ntse ba ithuta. Se, se na le ditlamorago tse di sa itumedising ka go se bonolo e bile go sena netefaletso ya gore ba tlaa bona diphatlatiro tseo. Se, se tsisa kgatelelo go dikolo tsa dithuto tse di kgolo le mafapha ka bangwe ikgatholosa lenaane le. Botlhokwa jwa dipatlisiso tse, bo ikaelela go araba dipotso tse di latelang: - A go botlhokwa go nna le lenaane la go ikatisetsa tiro o ntse o ithuta ka gangwe mo serutweng sa "Town and Regional Planning" mo lenaaneng la thuto? - Fa go ka fitlhelwa e le gore lenaane le le tshwanelwa ke go dirisiwa, baithuti ba lo simolole leng? - Gape ba lo dire lobaka lo lo kana kang? Dipatlisiso tse, di fana ka diphitlhelelo tse di tseneletseng tse di ikaelelang go bona tharabololo ka lenaane, le go baithuti le badirammogo ba ba thusitseng ka dikakanyo. Se, ke karolo ya dingangisano tse di tsweletseng ka dithuto tse di maleba tsa thuto.
Keywords: South African Higher Education Qualifications Framework (HEQF); Work-Integrated Learning (WIL)